Clinical Manifestations and Outcomes of Renal Transplantation Patients With Pneumocystis jirovecii Pneumonia and Cytomegalovirus Co-infection - Zou, Jilin; Qiu, Tao; Zhou, Jiangqiao; Wang, Tianyu; Ma, Xiaoxiong; Jin, Zeya; Xu, Yu; Zhang, Long; Chen, Zhongbao (Frontiers in Medicine, 2022)
Background: Pneumocystis jirovecii pneumonia (PJP) and cytomegalovirus (CMV) infection are common opportunistic infections among renal transplantation (RT) recipients, and both can increase the risk of graft loss and patient mortality after RT. However, few studies had evaluated PJP and CMV co-infection, especially among RT patients. Therefore, this study was performed to evaluate the impact of CMV co-infection with PJP among RT recipients. Methods: We retrospectively analyzed the clinical data of patients with confirmed diagnosis of PJP between 2015 and 2021 in our hospital. We divided patients into PJP and PJP+CMV groups according to their CMV infection status, and the clinical severity and outcomes of the two groups were evaluated. Results: A total of 80 patients after RT were diagnosed with PJP. Of these, 37 (46.2%) patients had co-existing CMV viremia. There were no statistically significant intergroup differences in age, sex, diabetes, onset time of PJP after RT and postoperative immunosuppressant. Compared to serum creatinine (Cr) at admission, the serum Cr at discharge in both the PJP and PJP+CMV groups were decreased. The PJP+CMV group had a higher C-reactive protein level, higher procalcitonin level, and lower albumin level than the PJP group. The PJP+CMV group showed a higher PSI score than the PJP group. Moreover, the initial absorption time of the lesion was longer in the PJP+CMV group. However, the duration of hospitalization showed no significant differences between the two groups. The mortality rate was 9.4-times higher in the PJP+CMV group than in the PJP group. The rate of admittance to the intensive care unit was 3.2-times higher in the PJP+CMV group than in the PJP group. Conclusion: CMV co-infection may result in more serious inflammatory response. RT patients with PJP+CMV infection had more severe clinical symptoms, slower recovery from pneumonia, and higher mortality than those with PJP alone. Therefore, when RT patients present with severe PJP, the possibility of CMV co-infection should be considered. Short-term withdrawal of immunosuppressants in case of severe infection is safe for the renal function of RT patients.